Modelling of anisotropic work-hardening behaviour of metallic materials subjected to strain-path changes - Bouvier, S. (2005)
The present paper aims at reviewing some recent progress in developing advanced constitutive models which are devoted to the description of the anisotropic work-hardening behaviour under strain-path changes at large strains of metallic materials. After reviewing some microscopic and macroscopic experimental evidence, a physically-based phenomenological model using four internal state tensor variables is presented. This model can be simplified into several classical phenomenological models in order to take into account either the isotropic or the kinematic hardening or both. The implementation of the proposed models in the in-house finite element code DD3IMP is briefly recalled. Numerical simulations of the stamping of a curved rail are carried out in order to evaluate the accuracy and the efficiency of the proposed models in modelling the springback.